2016
DOI: 10.1002/fut.21796
|View full text |Cite
|
Sign up to set email alerts
|

Do Scheduled Macroeconomic Announcements Influence Energy Price Jumps?

Abstract: For six important energy futures markets, this study examines whether large price movements (i.e., jumps) are related to the arrival and information content of scheduled macroeconomic announcements. Since prior studies by Kilian and Vega [(2011) Review of Economics and Statistics, 93, 660–671] and Chatrath, Miao, and Ramchander [(2012) Journal of Futures Markets, 32, 536–559] find little evidence of an announcement‐price reaction in mean energy returns, we focus on jump dynamics as a possible conduit for macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 62 publications
(166 reference statements)
2
8
0
Order By: Relevance
“…The coefficient for ANNxPOL t further indicates that the real‐time trading of USDA reports increases jump size, which is essentially due to the jump clustering in the real‐time era. Overall, the notion that jump behavior is influenced by surprises is consistent with the studies that have explored the impact of various forms of news on intraday price jumps in financial markets (Jiang, Lo, and Verdelhan ; Boudt and Petitjean ; Bjursell, Gentle, and Wang ; Chan and Gray ).…”
Section: Empirical Design and Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The coefficient for ANNxPOL t further indicates that the real‐time trading of USDA reports increases jump size, which is essentially due to the jump clustering in the real‐time era. Overall, the notion that jump behavior is influenced by surprises is consistent with the studies that have explored the impact of various forms of news on intraday price jumps in financial markets (Jiang, Lo, and Verdelhan ; Boudt and Petitjean ; Bjursell, Gentle, and Wang ; Chan and Gray ).…”
Section: Empirical Design and Resultssupporting
confidence: 81%
“…Increased speed not only brought new types of traders into the market but also changed the way conventional traders operate as they adapt to the new low latency environment (O'Hara 2015). After the adoption of the new platform, the Commodity Futures Trading Commission (CFTC) identified a number of large price movements or "flash" events in the corn futures market between 2010 and 2015, which raised concerns about the price risk faced by market participants (CFTC 2015). Some traditional commodity investors have already announced company closures due to their inability to react quickly and effectively to increased price risk (Meyer 2018;Onstad 2018).…”
mentioning
confidence: 99%
“…However, Adrangi, Chatrath, Christie‐David, Hong, and Ramchander () rationalize that macroeconomic news has little effect on immediate supply and demand of commodities, and have no bearing on contemporary prices. Thus, we can expect to find a long‐term, rather than a short‐term (Chan & Gray, ), relationship between news and commodity futures. By employing the GARCH‐MIDAS framework proposed in Engle, Ghysels, and Sohn (), we decompose commodity volatilities into their short/long‐term components, where the latter are affected by news‐based uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…By and large, this body of work studies the impact of macroeconomic news on the price/level of the asset. There is also considerable evidence that macroeconomic announcements are related to price jumps (Beber & Brandt, ; Chan & Gray, ; Huang, ; Lahaye, Laurent, & Neely, ; Rangel, ). However, a less obvious channel through which news can exert influence is via volatility jumps.…”
Section: Introductionmentioning
confidence: 99%
“…We focus on a set of four influential macroeconomic variables: the Federal Open Market Committee's (FOMCs) announcement of the target Federal Funds rate, non‐farm payroll (NFP), the unemployment rate, and the producer price index (PPI). Noting that prior studies have shown that the release of these economic reports significantly impacts jumps in asset prices (Beber & Brandt, ; Chan & Gray, ; Huang, ; Rangel, ), it is plausible that these same news releases also drive volatility jumps. To assess the impact of macroeconomic news announcements across different financial assets, we test for volatility jumps in a range of U.S. Treasury securities and the S&P500 equity index.…”
Section: Introductionmentioning
confidence: 99%